Dermal drug selection and development : an industrial perspective - Trottet, Lionel (Springer, 2017)
The authors show how the pharmaceutical industry faces the development of dermal drugs and provide the only book of its kind that describes how the industry develops and selects dermal drugs, complete with the challenges and opportunities of the field. Delivery of drugs through the skin has been an attractive and challenging area for research, and advances in modern technologies have resulted in a larger number of drugs being delivered transdermally, including conventional hydrophobic small molecule drugs, hydrophilic drugs and macromolecules. Offering the perspective from the industrial side of selection and development of drugs, the primary audience is geared towards the pharmaceutical industry but can also offer valuable information to clinicians, compounding pharmacists, and similarly pharmacy students. Dermal Drug Selection and Development covers the scientific gaps that exist in terms of dermal pharmacokinetics and the resulting uncertainty by clinicians when choosing a drug candidate.
5.1.4 Suction Blister.
Keywords: Transdermal medication.; elektronické knihy; electronic books